From hepatitis C virus infection to B-cell lymphoma. (10th October 2017) - Couronné, L; Bachy, E; Roulland, S; Nadel, B; Davi, F; Armand, M; Canioni, D; Michot, J M; Visco, C; Arcaini, L; Besson, C; Hermine, O
Abstract: In addition to liver disorders, hepatitis C virus (HCV) is also associated with extrahepatic immune manifestations and B-cell non-Hodgkin lymphoma (NHL), especially marginal zone lymphoma, de novo or transformed diffuse large B-cell lymphoma and to a lesser extent, follicular lymphoma. Epidemiological data and clinical observations argue for an association between HCV and lymphoproliferative disorders. The causative role of HCV in NHL has been further supported by the response to antiviral therapy. Pathophysiological processes at stake leading from HCV infection to overt lymphoma still need to be further elucidated. Based on reported biological studies, several mechanisms of transformation seem however to emerge. A strong body of evidence supports the hypothesis of an indirect transformation mechanism by which sustained antigenic stimulation leads from oligoclonal to monoclonal expansion and sometimes to frank lymphoma, mostly of marginal zone subtype. By infecting lymphocytes, HCV could play a direct role in cellular transformation, particularly in de novo large B-cell lymphoma. Finally, HCV is associated with follicular lymphoma in a subset of patients. In this setting, it may be hypothesized that inflammatory cytokines stimulate proliferation and transformation of IgH–BCL2 clones that are increased during chronic HCV infection. Unraveling the pathogenesis of HCV-related B-cell lymphoproliferation is of prime importance to optimize therapeutic strategies, especially with the recent development of new direct-acting antiviral drugs.